Dragon Quest monsters+. 3 - Yoshizaki, Mine (Seven Seas Entertainment, 2019)
Back in the Kingdom of GreatTree, Kleo is challenged by Dino, another Monster Master from the next kingdom over who wants to prove himself and his monsters by defeating Kleo.